Peran Pembiayaan Murabahah dalam Pemberdayaan UMKM di KSPPS Yaummi Maziyah Assa’adah Cabang Trangkil - Diah Martiana (JIOSE: Journal of Indonesian Sharia Economics, 2026)
Micro, Small, and Medium Enterprises (UMKM) play a crucial role in the national economy; however, they continue to face major constraints, particularly limited access to financing. Sharia Microfinance Institutions, such as Savings and Financing Cooperatives (KSPPS), provide alternative financing solutions based on Islamic principles, one of which is through the murabahah contract. This study aims to analyze the role of murabahah financing in empowering UMKM and to identify the supporting and inhibiting factors in its implementation at KSPPS Yaummi Maziyah Assa’adah Trangkil Branch. This study employs a descriptive qualitative approach using a field research method. Data were collected through interviews, observations, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The results indicate that murabahah financing contributes to increasing business capital, enhancing business capacity, and promoting members’ economic independence. However, its impact on business sustainability has not been optimal due to limited mentoring and supervision. Supporting factors include ease of access to financing, the application of Sharia principles, and members’ business experience. Meanwhile, inhibiting factors include limited human resources, insufficient business mentoring, and fluctuations in UMKM income. This study emphasizes the importance of integrating financing and mentoring in the empowerment of MSMEs within the framework of Islamic microfinance.